Occurrence of the bentfin devil ray, Mobula thurstoni (Chondrichthyes : Mobulidae), in the western Atlantic - Gadig, OBF; Namora, R. C.; Motta, F. D. (Cambridge University Press, 2003)
This paper reports the occurrence of the fifth species of Mobula in the western Atlantic, M. thursloni, based on specimens caught by artisanal and driftnet fisheries in coastal waters off southern Brazil.